A inconstitucionalidade da criminalização das casas de prostituição e demais atividades de lenocínio - Alessandra Margotti dos Santos Pereira (2016)
This dissertation aims to analyze the legal and constitutional reasons for the criminalization of pimping activities. On the assumption that prostitution is a legal occupation, officially recognized by the Ministry of Labor and Employment, and that the criminal law should prohibit only those conducts that harm legal rights, therefore resulting in victims, this work sought to show that such criminalization is based only in moral and religious aspects. In order to do so, an analysis on the concepts of legal rights and the principle of harmfulness, under the Democratic State of Laws paradigm, is made, demonstrating the paternalistic role of the State and at what point it should be avoided. With the growing demand of sex workers associations for the regulation of prostitution and the activities that exploit it economically, this work takes a very important role, in the extent that intends to demonstrate how such criminalization is unconstitutional and affects basic rights of people who choose to prostitute themselves. Despite the intention to protect, this criminalization offends the autonomy, the self-determination and the sexual freedom of those professionals who have all kinds of rights mitigated by a moralistic and paternalistic role of the State. It is important to highlight that what is defended here is the legalization of pimping activity regarding the prostitution of majors, people capable and consenting to the activity, considered sex workers, and not under no circumstances - of children and adolescents or people who prostitute themselves through any kind of violence or abuse, which should be widely fought against.